Empirical approach to the gender gap in students’ reading consumption in international contexts - Trigo Ibáñez, Ester; Santos Díaz, Inmaculada Clotilde (Frontiers in Psychology, 2023)
Reading is a very important aspect today, which is why it is a recurring topic in research. This study aims to analyze the gender gap in the reading consumption of adolescents and compare the situation in Spain with that of other countries. It addresses, for the first time, the influence of the gender factor on the reading habits of adolescents who have just begun secondary education. This is an empirical study carried out based on the research projects “Determining factors in the reading habits of secondary education students. A study from the variables of the educational context” and “Reading habits in international contexts of Secondary Education students. A study of educational practices to promote reading.” It is based on the hypothesis that reading consumption is conditioned by gender and country-specific educational policies and, therefore, by the place where the study is carried out. To do this, an international sample of students was taken as a reference, made up of a matrix group of Spanish students contrasted with small samples from three different countries that we are interested in comparing with the Spanish context: Portugal, Poland, and Chile. The results have shown that the gender gap in reading is perceived in all the contexts studied and that it increases in contexts with less developed co-education programs; therefore, it is necessary to implement effective policies in the educational field to eliminate the existence of gender stereotypes.